The Kharbarelli Pick-Up: How & Why This Throwing Technique Works - Scott, Steve (Revista de Artes Marciales Asiáticas, 2012)
The throwing technique that came to be known as the Kharbarelli Pick-up in the world of competitive judo is a good example of how different cultures and their unique grappling traditions have changed the look of this Olympic sport. This presentation of the Kharbarelli Pick-up illustrates and explains the theory, mechanics, and application of this unorthodox, effective and crowd-pleasing throwing technique. The author has an extensive background in sambo and judo and studied this technique for a number of years after seeing it used in international judo and sambo events. The Kharbarelli Pick-up, while considered “unorthodox” and not Japanese in origin, is effective because it exhibits the common elements of using an opponent’s balance and movement in the same way a “traditional” judo throw does.